2019
DOI: 10.1155/2019/4864370
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Common Variants in HFE and TMPRSS6 Genes with Hepcidin-25 and Iron Status Parameters in Patients with End-Stage Renal Disease

Abstract: Background. Influence of TMPRSS6 A736V and HFE (C282Y and H63D) polymorphisms on serum hepcidin-25 levels and iron status parameters in end-stage renal disease (ESRD) patients stratified according to gender has not been previously investigated. In addition, we aimed to evaluate the diagnostic accuracy of the parameters to separate iron-deficiency anemia (IDA) from anemia of chronic disease. Materials and Methods. Iron status parameters and genetic analysis were performed in 126 ESRD patients and in 31 IDA pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Meanwhile, TMPRSS6 polymorphism of rs855791 was also reported among CKD patients [23]. Recent research had also linked TMPRSS6 gene polymorphism to higher hepcidin levels in end-stage renal disease [22].…”
Section: Tmprss6 Snps Associated With Other Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, TMPRSS6 polymorphism of rs855791 was also reported among CKD patients [23]. Recent research had also linked TMPRSS6 gene polymorphism to higher hepcidin levels in end-stage renal disease [22].…”
Section: Tmprss6 Snps Associated With Other Diseasesmentioning
confidence: 99%
“…Due to the polymorphisms arising in the TMPRSS6 gene, these variants affect the catalytic activity domain of MT-2 and, thus, unable to suppress the hepcidin expression, causing a high level in the circulation, thus leading to anaemia due to lack of plasma iron [21]. Recent studies demonstrated that TMPRSS6 gene polymorphisms were associated with elevated hepcidin levels in end-stage renal failure [22] and chronic kidney disease patients with IDA [23]. Mutations in the TMPRSS6 gene were also reported in patients with IRIDA, a rare autosomal recessive disorder in which the hepcidin levels were shown to be elevated [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Iron is essential for metabolic processes like oxygen transport, deoxyribonucleic acid (DNA) synthesis, electron transport, as well as cellular functions can affect one's well-being [102]. In individuals with obesity, the chronic inflammatory state related to obesity might be a possible risk factor for iron deficiency, which is also called the anemia of inflammation [57,[103][104][105]. Studies have shown that the prevalence of iron deficiency in adults with obesity is remarkable, and a decrease in serum iron and transferrin saturation levels is inversely associated with an increase in body mass index [103,[106][107][108].…”
Section: Ironmentioning
confidence: 99%
“…A GWAS concluded that identifying mutations in the TMPRSS6 gene has broad applications in understanding clinical disorders of iron metabolism, and polymorphisms in TMPRSS6 gene may contribute to iron deficiency anemia (IDA) in individuals even in absence of other predisposing factors for IDA [112]. Studies have shown a common TMPRSS6 gene variant to be prevalent in 45% of the individuals without iron deficiency and clinically relevant inflammatory conditions [104] and 36.5-41.7% in a group of nonpregnant women [113]. TF and human hemochromatosis (HFE) genes are involved in genetic regulation of maintenance of iron homeostasis [37].…”
Section: Ironmentioning
confidence: 99%
“…There is a need to understand the genetic factors associated with iron deficiency anemia in pregnant women [20]. Matriptase-2 is important and down-regulate hepcidin expression through cleaving membrane-bound hemojuvelin, which can enhance hepcidin transcription [21]. The reported causative mutations in TMPRSS6 are spread throughout the gene sequence, disrupting the catalytic activity or protein-protein interactions [22].…”
Section: Introductionmentioning
confidence: 99%